1996
DOI: 10.1116/1.588593
|View full text |Cite
|
Sign up to set email alerts
|

Extendibility of synchrotron radiation lithography to the sub-100 nm region

Abstract: Studies on correction accuracy of proximity effect for the pattern area density method in electron beam direct writing J.This article discusses the resolution of synchrotron radiation lithography in the sub-100 nm region, taking into consideration the mass production of large-scale integrated circuits, under attainable conditions for the x-ray mask, proximity gap, and resist processes. Resolution and exposure latitude for line-and-space patterns are markedly improved by using a mask with a contrast of only 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The extendibility of this technology to the sub-100 nm region has been investigated by carrying out exposure tests for line-and-space patterns, isolated lines, and dynamic random access memory ͑DRAM͒-like and static random access memory-like patterns. [4][5][6] These results indicate that performance of PXL for the mass-fabrication of ULSIs at advanced technology nodes has improved appreciably.…”
Section: Introductionmentioning
confidence: 99%
“…The extendibility of this technology to the sub-100 nm region has been investigated by carrying out exposure tests for line-and-space patterns, isolated lines, and dynamic random access memory ͑DRAM͒-like and static random access memory-like patterns. [4][5][6] These results indicate that performance of PXL for the mass-fabrication of ULSIs at advanced technology nodes has improved appreciably.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one can expect to obtain patterns with higher resolution by means of X-ray lithography [25]. However, the high photon cost and the need for heating or reactive gas are problems to be solved for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…The most critical issue involving the X-ray mask is considered by many researchers to be image placement accuracy. Although the required image placement accuracy is 12 nm in 30 for the 100-nm design rule, the one achieved now is about 50 nm at NTT and the one reported is about 30 nm [5]. To improve this, much efforts are required to find methods reducing mask distortion.…”
Section: Goal and Challengesmentioning
confidence: 79%
“…Deguchi demonstrated that a 70 nm line-and-space pattern can be replicated with a gap of less than 15 pm as Fig. 9(a) shows [5]. The good depth-of-focus allows us to fabricate the high aspect ratio pattern in Fig.…”
Section: Application To Lsimentioning
confidence: 87%
See 1 more Smart Citation